ANEMIA AND RHEUMATOID ARTHRITIS - Vatutin, M.T.; Kalinkina, N.V.; Smyrnova, G.S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The represented analysis of literature is dedicated to the problem of anemia development at rheumatoid arthritis (RA), which develops in 36-65% of cases. It is accompanied hypoxia of tissues and can, on the one hand lead to damage of various organs and systems, and with another – to deterioration of a clinical course and the prognosis of the patient. Pathogenetic mechanisms of an anaemia in RА: change of a metabolism of iron, life shortening of erythrocyte, or their inadequate production a bone marrow, a role of proinflammatory cytokines, drugs and genetic factors. We investigated the role of those medicines, which is used in the treatment of this pathology and improved quality of life.